The Influence of Leader Humor on Job Crafting in Mediation By Perception of Organizational Support and Work Engagement Employees Secretariat DPRD Riau Province - Yon Elfi; Adi Rahmat; Arizal (SAINS ORGANISASI, 2023)
The purpose of this study was to determine the influence of Humor Leadership on Job Crafting mediated by Organizational Support and Work Engagement of DPRD Secretariat Employees of Riau Province. The population in this study were all employees at the Riau Provincial DPRD Secretariat with a sample of 100 respondents, where the sample was taken using a purposive sampling method, namely selecting samples based on certain criteria or considerations. Data collection techniques using questionnaires and dissemination using Google Forms. The data analysis technique in this study was Structural Equation Modelling (SEM) using SmartPLS 3.0 as a data processing tool. The results of this study indicate that humorous leadership has a positive and significant effect on Perception of Organizational Support, work engagement and job crafting at the Riau Provincial DPRD Secretariat, Perception of Organizational Support and work engagement has a positive and significant effect on Job Crafting at the Riau Provincial DPRD Secretariat. The results of the study also show that Perception of Organizational Support and work engagement are able to mediate the relationship between humorous leadership and Job Crafting at the Secretariat of DPRD Riau Province.